2022
DOI: 10.3390/jof8080842
|View full text |Cite
|
Sign up to set email alerts
|

Amazing Fungi for Eco-Friendly Composite Materials: A Comprehensive Review

Abstract: The continually expanding use of plastic throughout our world, along with the considerable increase in agricultural productivity, has resulted in a worrying increase in global waste and related environmental problems. The reuse and replacement of plastic with biomaterials, as well as the recycling of agricultural waste, are key components of a strategy to reduce plastic waste. Agricultural waste is characterized as lignocellulosic materials that mainly consist of cellulose, hemicellulose, and lignin. Saprobe f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
70
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(93 citation statements)
references
References 111 publications
22
70
0
1
Order By: Relevance
“…However, the lowest degree of density was obtained from MBCs made from rice straw and S. commune. It was found that the obtained density values in this study were within the ranges described in previous reports at 25 to 954 kg/m 3 [19,21,26,35,36,39,[46][47][48]. The results of this study are supported by the findings of several previous studies, which reported that the density of MBCs was significantly influenced by substrate type and fungal species [19,21,26,42].…”
Section: Densitysupporting
confidence: 90%
See 4 more Smart Citations
“…However, the lowest degree of density was obtained from MBCs made from rice straw and S. commune. It was found that the obtained density values in this study were within the ranges described in previous reports at 25 to 954 kg/m 3 [19,21,26,35,36,39,[46][47][48]. The results of this study are supported by the findings of several previous studies, which reported that the density of MBCs was significantly influenced by substrate type and fungal species [19,21,26,42].…”
Section: Densitysupporting
confidence: 90%
“…Saprobic fungi can degrade lignocellulosic residues into nutrients through certain bio-fabricated processes wherein their mycelia networks can effectively combine substrate particles together [18]. Ganoderma, Pleurotus, Pycnoporus, and Trametes are the most commonly used fungal genera in the production of MBCs [19][20][21]. Interestingly, MBCs have successfully been employed in the development of mycelium-based materials that can be applied in the construction of buildings and in the manufacturing of furniture, packaging, and various other household items [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations